Feasibility of spoof surface plasmon waveguide enabled ultrathin room temperature THz GaN quantum cascade laser. Issue 1661 (13th February 2014) - Sun, Greg; Khurgin, Jacob B.; Tsai, Din Ping
Abstract: We propose and study the feasibility of a THz GaN/AlGaN quantum cascade laser (QCL) consisting of only five periods with confinement provided by a spoof surface plasmon (SSP) waveguide for room temperature operation. The QCL design takes advantages of the large optical phonon energy and the ultrafast phonon scattering in GaN that allow for engineering favorable laser state lifetimes, and the SSP waveguide provides the optical confinement for the ultrathin QCL. Our analysis has shown that the waveguide loss is sufficiently low for the QCL to reach its threshold at the injection current density around 6 kA/cm 2 at room temperature.